An Overview of the Intelligence of the Deaf Students in SLB B Purwokerto - Qurrataayun, Alif; Wahidah, Fatin Rohmah Nur; Nur’aeni, Nur’aeni; Na’imah, Tri (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2022)
Intelligence is a measure of student intelligence, when students have high intelligence, there is good learning. Intelligence in deaf students is very difficult to measure because most of the measuring instruments used use verbal functions, on the other hand many SLB B teachers complain that their students experience academic decline. This happens because most teachers do not know the intelligence of their students so that teachers give treatment with the same portion when learning takes place. The purpose of this study is to provide an overview of the intelligence of deaf students at SLB B Purwokerto. The data collection method used was the saturated sample technique so that 30 participants were obtained. Based on the results of the criterion validity test, it was obtained that r = 0.465 so that the cpm test and the bender-gestalt test were declared valid. The results of the CPM test reliability test (α cronbach = 0.889) on the Bender-Gestalt test (α cronbach = 0.789). The correlation test showed that there was a significant correlation between the cpm test and the bender-gestalt test. In the CPM test, the non-verbal reasoning grade on deaf students is in group IV below average intellectual capacity and students with superior grade I are male.